STRATEGI NAIKAN OMZET LEWAT ONLINE - Syarifudin Syarifudin; Aditya Riky Nugroho; Antania Shinta Yuwono; Suripto Suripto; Syamsul Asmedi (S1 Accounting Program, Universitas Pamulang, 2019)
Community service is an activity that aims to help certain communities in some activities without expecting anything in return. In general, this program is designed by various universities or institutes in Indonesia, one of which is Pamulang University. to make a real contribution to the Indonesian people, especially in developing the welfare and progress of the Indonesian people. Community Service Activities is one part of the Higher Education Tri Dharma. The form of activities in the implementation of community service in Jampang village is to transfer technology with the theme of raising the turnover strategy online. The instructors and resource persons involved were Accounting Study Program Lecturers from Pamulang University. The results of the PKM Implementation conducted on 20.21 and 22 September 2019 were adding to their knowledge in economics, owing to marketing, the participants of the ornamental fish group in Jampang were very enthusiastic about the material they got from accounting lecturers at Pamulang University, the participants can immediately practice selling via online, the response of the participants is very good and happy because it is very helpful in learning about how to sell via online.Very useful in carrying out marketing or sales strategies via the internet. according to a survey conducted by SWA Indonesia is the second largest in the world as a user of Facebook and Twitter and is very promising for online marketing, moreover supported by the ease of obtaining mobile phones. The internet has an appeal for consumers because it has advantages such as convenience, having access 24 hours a day, alternative efficiency space, unlimited area coverage. Online Marketing or Online Marketing has actually been carried out by Fish Farmers in Jampang Village, Kemang District, Bogor Regency, but has not been optimal in its management. So that it does not work well. To optimize marketing through online, on Sunday September 22 2019, community service activities in Jampang Village are carried out in the form of socialization related to